Industrial air pollution and mortality in the Taranto area, Southern Italy: A difference-in-differences approach. (November 2019) - Leogrande, Simona; Alessandrini, Ester Rita; Stafoggia, Massimo; Morabito, Angela; Nocioni, Alessandra; Ancona, Carla; Bisceglia, Lucia; Mataloni, Francesca; Giua, Roberto; Mincuzzi, Antonia; Minerba, Sante; Spagnolo, Stefano; et al.
Abstract: Background: A large steel plant close to the urban area of Taranto (Italy) has been operating since the sixties. Several studies conducted in the past reported an excess of mortality and morbidity from various diseases at the town level, possibly due to air pollution from the plant. However, the relationship between air pollutants emitted from the industry and adverse health outcomes has been controversial. We applied a variant of the "difference-in-differences" (DID) approach to examine the relationship between temporal changes in exposure to industrial PM10 from the plant and changes in cause-specific mortality rates at area unit level. Methods: We examined a dynamic cohort of all subjects (321, 356 individuals) resident in the Taranto area in 1998–2010 and followed them up for mortality till 2014. In this work, we included only deaths occurring on 2008–2014. We observed a total of 15, 303 natural deaths in the cohort and age-specific annual death rates were computed for each area unit (11 areas in total). PM10 and NO2 concentrations measured at air quality monitoring stations and the results of a dispersion model were used to estimate annual average population weighted exposures to PM10 of industrial origin for each year, area unit and age class. Changes in exposures and in mortality were analyzed using Poisson regression. Results: We estimated an increased risk in natural mortality (1.86%, 95% confidence interval [CI]: −0.06, 3.83%) per 1 μg/m 3 annual change of industrial PM10, mainly driven by respiratory causes (8.74%, 95% CI: 1.50, 16.51%). The associations were statistically significant only in the elderly (65+ years). Conclusions: The DID approach is intuitively simple and reduces confounding by design. Under the multiple assumptions of this approach, the study indicates an effect of industrial PM10 on natural mortality, especially in the elderly population. Highlights: We applied a variant of the "difference-in-difference" approach (DID). The DID approach is intuitively simple and reduces confounding by design. We examined the relationship between exposure to industrial PM10 and mortality. We found an effect of industrial PM10 on natural and respiratory mortality. The associations were stronger in elderly (65+ years) than in the other age groups.